2017
DOI: 10.1007/s00380-017-0965-8
|View full text |Cite
|
Sign up to set email alerts
|

A longer total duration of rapid ventricular pacing does not increase the risk of postprocedural myocardial injury in patients who undergo transcatheter aortic valve implantation

Abstract: Rapid ventricular pacing (RVP) is used during transcatheter aortic valve implantation (TAVI). RVP disturbs myocardial oxygen balance, and when prolonged, it may cause procedure-related myocardial injury (PMI). This study investigated whether a longer duration of RVP increased the occurrence of PMI or worsened long-term mortality after TAVI. We retrospectively analyzed data from 188 patients who underwent TAVI in our institute from January 2013 to July 2015. Myocardial injury was represented by the peak value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…As a result, cardiac output drops and causes transient coronary hypoperfusion and systemic hypotension, a condition that can lead to myocardial stunning [33]. Following TAVI cardiac biomarkers sensitive for myocardial injury increase and are valid surrogates for poor long-term outcomes [32,33]. But interestingly, the duration of rapid ventricular pacing itself seems to have no relevant correlation with periprocedural myocardial injury, defined by the elevation of ischemic markers [32].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, cardiac output drops and causes transient coronary hypoperfusion and systemic hypotension, a condition that can lead to myocardial stunning [33]. Following TAVI cardiac biomarkers sensitive for myocardial injury increase and are valid surrogates for poor long-term outcomes [32,33]. But interestingly, the duration of rapid ventricular pacing itself seems to have no relevant correlation with periprocedural myocardial injury, defined by the elevation of ischemic markers [32].…”
Section: Discussionmentioning
confidence: 99%
“…As with any hypotensive period, RVP may have adverse clinical impact. However, even though RVP is routinely performed during the majority of TAVR procedures, current data on the clinical impact of RVP during TAVR are limited to small numbers of patients with surrogate end points 1, 2, 4, 7. Few studies have correlated RVP with a clinical end point.…”
Section: Discussionmentioning
confidence: 99%
“…Okitsu et al assessed correlation between RVP and elevation in myocardial biomarkers4 and found good correlation between duration of RVP and elevation of myocardial biomarkers, however, once corrected to TAVR approach (ie, femoral versus apical) no significant correlation was found between pacing duration and elevation in myocardial biomarkers. Indeed prior studies have shown that transapical approach is associated with higher levels of cardiac enzymes 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В 2017 г. K. Okitsu et al [106] опубликовали исследование, посвященное изучению влияния продолжительности проведения RVP на интраоперационное ишемическое повреждение миокарда и послеоперационную летальность. Обследованы 188 пациентов, которым проводили транскатетерное протезирование аортального клапана (trans-catheter aortic valve implantation, TAVI).…”
Section: управляемая желудочковая тахикардияunclassified